Left and right in the nineteenth ideological debate: the case of Portugal - Martins, Pedro Miguel Páscoa Santos (2013)
In the study of Portuguese political thought, the dichotomic distinction between right and left has been something intuitively accepted. Gathered from the works of historians, political scientists and philosophers, the different criteria, ideas, positions and movements that help to shape it are, nevertheless, seldom submitted to explanation. Be it as it may, at different historical settings, the labels right and left have not always corresponded to the same political forces. In the groundbreaking and rich period between 1820 and 1910, a true nurturing soil for Portuguese rightist and leftist ideologies, three major political families were confronted, naturally showing corresponding internal ideological nuances: liberal monarchism, republicanism and different types of socialism / anarchism. In order to define what movements and / or what political and party forces materialized the political spectrum during this political setting, we assume a simple criterion: the degree of equality demanded in relation of civic, political and social rights. We will necessarily have to take into account what is the existing conception of equality in that society. Between 1820 and 1848, the liberalism born out of the upheavals of the 20’s and the September revolution, stood for a clearly leftist political stance, and equalitarian and radical position in the defense of rights. Disregarding any intermediate positions in the political arch, the far right represented nostalgic absolutist monarchy and the cultured and moral society of the Ancient Regime. From 1848, due to different circumstances and the advent of different socialisms and republicanisms, this framework is altered. Republicanism came to be associated –at least for quite some time– to a leftist political stance as it propounded an equalitarian political ideology based upon universal suffrage. As the contradictions of capitalism and social and economical inequalities are revealed, republicanism no longer is the choice of the radical left in the face of different forms of socialism and anarchism. In differentiating right and left we must assume that the content of labels of both left and right are submitted to variation according to the historical political settings, we must assume their relativity (liberalism did not always represent the left), at the same time we must base our research in a solid and rather absolute criterion (the degree of equality in regards to social and citizenship rights) that we believe to be valid in establishing a clear differentiation.